(untitled) (Fiep Bulletin - online, 2014)
In Brazil, a growing number of researchers have been dedicated to studies of leisure. Currently, there are 128 research groups registered in the directory of the research CNPq studying the issue, and 64 of them related to the field of Physical Education. With the goal of providing a panoramic picture telling who are the authors who are producing, what the quantity and where is running what is being produced, we all researchers with evidence of doctors bound by these groups of research and mapping, from the curriculum of the Plataforma Lattes, their whole scientific production related to leisure. We classify in total, the production of 65 scientific researchers using the criteria of the CNPq for scores of types of scientific production (Articles international, national, books and chapters in books) and the criteria of the program QUALIS Capes for the classification of journals. At the end built a table listing the authors and numbers on the types of productions.